Beyond Cognition to Commitment: English Language Teaching in South Korean Primary Schools - MOODIE, IAN; FERYOK, ANNE (The Modern language journal (Boulder, Colo.), 2015)
In order to understand teacher cognition—the thoughts, beliefs, and knowledge of language teachers—it is helpful to understand why people commit to language teaching in the first place. However, few studies of language teachers have directly examined the nature and development of commitment in language teachers, across their language learning, teacher education, and teaching experience within their context. This study aims to do just that. Four primary school teachers in South Korea participated—two experienced teachers and two novice teachers—who at the time of the study were teaching English as a foreign language. Data from reflective writing, interviews, and classroom observations from a wider 18-month study on language teacher cognition and development were iteratively analyzed for the aims of this study. The findings show that commitment transfers between language learning and teaching through both positive and negative experiences, involves multiple and evolving intentions and mindsets in language teaching, and occurs in action in particular contexts. The findings also show that the teachers' early commitment to language learning contributed to their commitment to act on improving their English proficiency and classroom practices through professional development. The study concludes with implications and research suggestions.